EDUCATIONAL VALUE IN THE NOVEL RAIN BY TERE LIYE (A SOCIOLOGICAL STUDY OF LITERATURE) - Novianti, Hasmi; Febrina, Liga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Many authors express the problems of human life in literary works, because literature is a means of expressing ideas and feelings that exist in a person's heart. Religious or religious issues are expressed by the author in the story told through the characters. Moral issues related to human morals or manners. Social problems are reflected in community relations and other social classes. This is what underlies researchers to conduct this research. Cultural issues relate to human creativity, taste, and taste. The aim of the researcher in conducting this research is so that the researcher can obtain results about the value of education in the novel Rain by Tere Liye.This type of research is literary research using the Hermeneutics method with a literary sociology approach. The data collection technique used by researchers is by reading the entire story in the novel Rain by Tere Liye. Research data regarding the value of education. Data source for the novel Rain by Tere Liye. The four educational values ​​are the value of religious education, the value of moral education, the value of social education and the value of cultural education. From the research results, the value of social education was most often found by researchers. Based on the discussion of the issue of the value of education in the novel Rain by Tere Liye, the following conclusion can be drawn: The value of religious education contained in the novel Rain includes how to feel grateful, steadfast in facing various trials. Always ask Allah SWT for help. The religious education values ​​obtained in the novel Rain by Tere Liye amount to 4 religious education values.